Antifungal Activity of N-Hexane Extract of Duku Peel (Lansium domesticum Corr.) Against Candida albicans In Vitro - Humaira Fitriana; Trisnawaty K; Shanty Chairani (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2022)
Introduction: High colonization of Candida albicans in mouth can increase the risk of oral candidiasis. Duku peel (Lansium domesticum Corr.) has potential as antifungal material due to its terpenoid and phenolic content which can be extracted with n-hexane as solvent. Purpose: The purpose of this study is to determine the antifungal activity of n-hexane extract of duku peel against Candida albicans. Methods: This study used laboratorium experimental with post test only control group study design. Antifungal activity was determined using disc diffusion method on five sample groups: n-hexane extract of duku peel 15%, 20%, and 25%, nystatin as positive control, and aquadest as negative control. Antifungal activity was determined by measuring clear zone around the disc and measured with caliper in millimeter. The measurement of inhibition zone was analyzed with One Way ANOVA test. Results: There were no inhibition zone on n-hexane extract of duku peel with concentration of 15%, 20%, 25% and negative control while positive control had average inhibition zone diameter of 11,85 mm. Conclusion: N-hexane extract of duku peel with concentration of 15%, 20%, and 25% did not have antifungal activity against Candida albicans.